The Policy Cycle: a framework for knowledge management of practitioners' expertise and role in participatory processes - Edelmann, Noella; Albrecht, Valerie (Frontiers in Political Science, 2023)
There is extensive literature on stakeholder theory and knowledge management in the private sector, but less on the public sector, particularly in the context of public participation projects. Public participation initiatives are often designed using a case-by-case approach to identify relevant stakeholder groups, the engagement methods, and the tools to be used. In addition, public sector organizations (PSOs) often rely on participation experts and practitioners' professional knowledge to design successful participation projects. Given that public participation is to enable PSOs access to participants' knowledge, knowledge management is a central issue in public participation projects. In this multi-method, qualitative study we focus on the management of experts' and practitioners' knowledge, and we aim to show how their knowledge contributes to participatory processes and projects, and how the policy cycle can be used as a knowledge management framework to collect and structure their knowledge. We used sequential analysis to study the experiences of 84 practitioners from the public sector collected during a series of workshops. Our findings show the need to locate participation initiatives in the context of the government policy cycle, that the policy cycle can be used for knowledge management in public participation projects and to recognize that practitioners represent a key stakeholder group in public participation.